Penggunaan Bahasa Jurnalistik Penyaji Berita Cnn Indonesia Tanyangan Januari 2023 Dan Sebagai Rekomendasi Bahan Ajar DI SMP KelaS VII - Sholihah, Barokatus; Sutri, Sutri; Nuraini, Cut (Peneliti.net, 2024)
This research is motivated by the phenomenon commonly found in news presenters who deviate from proper language usage, which can have a negative impact on the future development of Indonesian language competence. The researcher conducted a study on the use of journalistic language by news presenters on CNN Indonesia's January 2023 broadcast and its potential as teaching material for Grade VII Junior High School. This research aims to help readers maintain and recall the importance of using correct journalistic language. The objectives are to describe the use of journalistic language by news presenters on CNN Indonesia's January 2023 broadcast and its potential as teaching material for Grade VII Junior High School. The object of this research is the use of journalistic language in the TV news broadcast on CNN in January 2023, obtained through the official website CNNIndonesia.com, while the subject is the news broadcast on CNN in January 2023. This research uses a descriptive qualitative method with observation as the data collection technique through note-taking. Data analysis employs the Direct Element Division technique. The findings of this research are as follows: 1) The news presenters on CNN Indonesia's January 2023 broadcast conform to the characteristics of journalistic language theory by Husen Mony (2020): simple, concise, clear, articulate, transparent, interesting, democratic, populist, and logical. They also adhere to the principle expressed in their jargon,